Renminbising China's foreign assets - Yin-Wong Cheung; Guonan Ma; Robert N. McCauley (Center for Economic Studies and ifo Institute (CESifo), 2010)
Since the 2008 global financial crisis, China has rolled out a number of initiatives to actively promote the international role of the renminbi and to denominate more of its international claims away from the US dollar and into the renminbi. This paper discusses the factors shaping the prospects of internationalising the renminbi from the perspective of the currency composition of China's international assets and liabilities. These factors include, among others, underlying valuation and management of the renminbi.
Keywords: F30; F31; F33; O24; 330; renminbi internationalisation; net international asset position; convertibility; exchange rate uncertainty; dollar peg; Konvertibilität; Währungsreserven; Auslandsvermögen; Wechselkurs; US-Dollar; China